A Brief Alcohol Intervention During Inpatient Psychiatric Hospitalization for Suicidal Adolescents. Issue 1 (February 2018) - McManama O'Brien, Kimberly H.; Aguinaldo, Laika D.; White, Erina; Sellers, Christina M.; Spirito, Anthony
Abstract: Alcohol use and suicide-related thoughts and behaviors are common in psychiatrically hospitalized adolescents and each problem can exacerbate the other. Despite knowledge about the functional relationship between alcohol use and suicide-related thoughts and behaviors, inpatient psychiatric units only cursorily address alcohol use because suicide risk is considered primary. In this paper we provide theoretical and empirical rationale for the inclusion of brief motivational interventions for alcohol use in inpatient treatment settings for suicidal adolescents. We give a case example of the brief intervention in practice, including when and how to use specific techniques. Following the case example, we discuss the flexibility of this intervention and how it can be adapted for adolescents with varying risk profiles. We conclude with recommendations for future research, including the development and testing of technology-based boosters following hospital discharge. Highlights: Rationale for brief motivational interventions for alcohol use in inpatient treatment for suicidal adolescents. Case example of the brief intervention in practice, including when and how to use specific techniques. Recommendations for future research, including development of technology-based boosters following hospital discharge.